1985
DOI: 10.1002/bjs.1800721204
|View full text |Cite
|
Sign up to set email alerts
|

Reticulo-endothelial function in rats with obstructive jaundice

Abstract: Reticulo-endothelial function was evaluated by measuring the biokinetics of a standardized 99mTc-sulphur colloid using scintillation camera technique in rats with biliary obstruction. There was no difference in the uptake of the colloid in the liver (K1) between sham operation and biliary obstruction at 1 week and 3 weeks. However, when corrected for changes in liver volume, the corrected colloidal uptake rate (cK1) of the liver was significantly decreased in 1 week's biliary obstruction (P less than 0.005 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 19 publications
4
10
0
2
Order By: Relevance
“…The change was much stronger than in group I and thus can not only be related to the operative procedure. It confirms the study of Tanaka et al [19] who showed a decrease in the liver uptake 1 week after bile duct occlu--Before obstruction (R = 11.7) = 6 days after biliary obstruction (R = 5.1) Fig. 6.…”
Section: Discussionsupporting
confidence: 81%
“…The change was much stronger than in group I and thus can not only be related to the operative procedure. It confirms the study of Tanaka et al [19] who showed a decrease in the liver uptake 1 week after bile duct occlu--Before obstruction (R = 11.7) = 6 days after biliary obstruction (R = 5.1) Fig. 6.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, prolonged biliary obstruction in the rat impairs the host defence system by depression of the reticuloendothelial system phagocytic activity [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Inadequate clearance of endotoxins in obstructive jaundice has been attributed to an altered reticuloendothelial system (RES) function of Kuppfer cells in the liver. 14,15 Recently, it has been demonstrated that, in isolated liver Kuppfer cells from cholestatic mice, increased numbers of viable intracellular bacteria after infection were present, suggesting an impaired intracellular bacterial killing. 16 The exact consequence with respect to development of infectious complications remains to be elucidated.…”
Section: Experimental Studiesmentioning
confidence: 99%